Evaluating the antagonist effect of naltrexone implant via opioid challenge tests with escalating doses of hydromorphone injection in former heroin dependent patients - Qu, Wei; Wang, Xuyi; Dong, Chongyang; Zhang, Tao; Yin, Shugui; Sun, Zhijun; Wang, Shiqiang; Guo, Anni; Hao, Wei (Frontiers in Psychiatry, 2025)
Opioid dependence is a serious, life-threatening condition with severe social impacts. Naltrexone (NTX) can weaken the effect of opioids and effectively reduce opioid self-administration, discrimination, and opioid-induced subjective effects, and the oral dosage form has been approved for the treatment of opioid dependence. However, the effectiveness of oral naltrexone as an opioid antagonist has been limited due to poor patient adherence. A long-acting formulation in the form of naltrexone implant (NTX-IMP) with a five-month duration of action may address this issue and improve outcomes. This study (trial registration number: CTR20181954) aimed to evaluate the effect, safety, and pharmacokinetics of NTX-IMP in agonist effects via hydromorphone challenge test, and to determine optimal dosages for future research. Thirty-one former opioid-dependent individuals were randomized to the 0.9g or the 1.5g NTX-IMP group. All subjects exhibited significant antagonistic effects during hydromorphone challenge test. Calculation of slope between VAS score or pupil diameter and hydromorphone dose suggested a stronger antagonistic effect in the 1.5 g group. Pharmacokinetic data suggested that effective plasma naltrexone concentration (≥1ng/ml) was detected from the third day for over 148 days, with higher concentration and longer duration in the 1.5 g group. All subjects tolerated NTX-IMP well. The findings indicate that the NXT-IMP effectively blocks the agonistic effects of hydromorphone in a dose-dependent manner.